Impact of COVID-19 pandemic on teaching learning process in pre clinical medical education in selective medical college in Bangladesh - Faruky, Kazi Salma Binte; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2024)
Background: The corona virus disease (COVID-19) pandemic has caused major disruption in educational sector including medical education. This disease outbreak has changed the medical education curriculum from traditional platform to elearning for students including Bangladesh. Objective: To observe the impact of COVID-19 pandemic on teaching learning process in medical education in Bangladesh. Methods: This qualitative survey was done among the 68 pre-clinical students aged 19 to 23years, of a non-government medical college in Bangladesh, from march to December 2021. All study participants were first year undergraduate MBBS students from anatomy, biochemistry and physiology. Data was collected by administering pre-tested questionnaires through Google form. Results: About 75% of the participants agreed that online classes were helpful during the home stay period of COVID pandemic, but about 92.2% of them were skeptical about the success of this online system for their future medical education. About 80.9% had difficulty in keeping their concentration during online class. About 94% found difficulty to follow online practical classes. Majority of the students (82.4%) feel anxious whether they were capable of doing their job properly since this method needs technical knowledge. About 50% students had limited access to internet, there were technical issues like power cut (76.5%), and poor network of internet (69.1%) also reduced the effectiveness of online education. Online class also disrupt teacher-student relationship. Conclusion: The internet based classes served the purpose of continuation of academic activity in medical education during adverse condition of COVID . But due to uneven use of technology it had some obstacles also. Student’s ability to learning in medical education was also hampered in the absence of physical classes. This online method of education system needs much improvement to be effective in medical education. J Bangladesh Soc Physiol 2022;17(2): 64-71